Potential study of Dillenia serrata Thunb. fruit extract from Bali Botanical Garden’s collection - I Putu Agus Hendra Wibawa; I Nyoman Lugrayasa; Sutomo (The East Java Biological Society, 2021)
Dillenia serrata Thunb.is a member of the Dillenia clan which is endemic to Sulawesi. D. serrata fruit is a seasonal fruit and can be used as a cooking ingredient as a sour taste, raw material for several food products such as candied fruit and syrup, and has the potential to be processed into chips and jam. Traditionally, the leaves and bark of D. serrata are also used by the local community as a sprue medicine, fever, wound medicine, treating swelling or inflammation and treating vomiting of blood. It is believed that there are still many untapped benefits from this plant. This study was conducted to determine the effectiveness of D. serrata fruit extract as an antimicrobial that causes disease in humans, and to determine its effectiveness as an antioxidant. The antioxidant test was carried out using the DPPH method while the antimicrobial test was carried out by the agar diffusion method (Kirby-Bauer). The ripe Dillenia fruit was extracted using methanol, the extract was then diluted in various concentrations for the DPPH test The results showed that the D. serrata extract had the ability as an antioxidant. The antioxidant activity of fresh fruit extracts was higher than that of dried fruit extracts. D. serrata extract is effective in inhibiting the growth of Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus mutans bacteria.